MIGA Annual Report 2016 - Multilateral Investment Guarantee Agency (Washington, DC, 2016)
In fiscal year 2016, despite a period of increased uncertainty over the state of our global economy, MIGA played a significant role in catalyzing private sector investments into countries most vulnerable to external shocks through our political risk insurance and credit enhancement products. Of the record $4.3 billion in guarantees issued, 53 percent of the investments were insured in poverty-afflicted areas. We continued to work tirelessly to ensure that we supported investments in fragile and conflict-affected countries, which make up 10 percent of our portfolio.